Spontaneous pneumomediastinum in a patient with marijuana use - Nutthakorn Horugsa; Jiyeon Kim; Samuel Kim; Judy Lalmuanpuii (European Journal of Case Reports in Internal Medicine, 2024)
The Macklin effect plays an essential role in the pathogenesis of spontaneous pneumomediastinum. It is the process by which is there is a blunt alveolar rupture that leads to air dissection through the bronchopulmonary sheaths and spreads into the mediastinum. Theoretically, marijuana use can cause spontaneous pneumomediastinum indirectly by inducing rigorous vomiting. We report a case of a healthy 22-year-old male with a history of recent marijuana use who presented with pneumomediastinum and rhabdomyolysis concurrently. After a thorough investigation, we concluded that this patient had spontaneous pneumomediastinum due to the Macklin effect from severe vomiting.